2016
DOI: 10.1088/2043-6262/7/1/015001
|View full text |Cite
|
Sign up to set email alerts
|

Targeted drug delivery nanosystems based on copolymer poly(lactide)-tocopheryl polyethylene glycol succinate for cancer treatment

Abstract: Along with the development of nanotechnology, drug delivery nanosystems (DDNSs) have attracted a great deal of concern among scientists over the world, especially in cancer treatment. DDNSs not only improve water solubility of anticancer drugs but also increase therapeutic efficacy and minimize the side effects of treatment methods through targeting mechanisms including passive and active targeting. Passive targeting is based on the nano-size of drug delivery systems while active targeting is based on the spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 14 publications
(22 reference statements)
2
10
0
1
Order By: Relevance
“…The differences in chemical structures among zein, zein-S-S-C 2 H 4 OH, zein-S-S-PTX_NP, and PTX were studied and compared using FTIR spectroscopy. In Figure , the fingerprints of zein were found at 3408 cm –1 , 2958 cm –1 , 1653 cm –1 , and 1540 cm –1 , which were attributed to the vibration stretching of the −OH group, the amide A′, the CO stretching of the amide I, and the C–N stretching of the amide II, respectively. , The fingerprints of PTX were found at 1734 and 1712 cm –1 , 1646 cm –1 , 1245 cm –1 , and 1074 cm –1 , which were corresponding to the CO stretching, CC stretching, C–N stretching, and CO stretching, respectively . Comparing the spectra of zein and zein-S-S-C 2 H 4 OH, it was observed that the peaks at 1017 cm –1 , 1045 cm –1 , and 1066 cm –1 , which were all corresponding to the symmetric stretching of the S–O bond, were shown in the spectra of zein-S-S-C 2 H 4 OH but not shown in that of zein.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The differences in chemical structures among zein, zein-S-S-C 2 H 4 OH, zein-S-S-PTX_NP, and PTX were studied and compared using FTIR spectroscopy. In Figure , the fingerprints of zein were found at 3408 cm –1 , 2958 cm –1 , 1653 cm –1 , and 1540 cm –1 , which were attributed to the vibration stretching of the −OH group, the amide A′, the CO stretching of the amide I, and the C–N stretching of the amide II, respectively. , The fingerprints of PTX were found at 1734 and 1712 cm –1 , 1646 cm –1 , 1245 cm –1 , and 1074 cm –1 , which were corresponding to the CO stretching, CC stretching, C–N stretching, and CO stretching, respectively . Comparing the spectra of zein and zein-S-S-C 2 H 4 OH, it was observed that the peaks at 1017 cm –1 , 1045 cm –1 , and 1066 cm –1 , which were all corresponding to the symmetric stretching of the S–O bond, were shown in the spectra of zein-S-S-C 2 H 4 OH but not shown in that of zein.…”
Section: Resultsmentioning
confidence: 93%
“…34,35 The fingerprints of PTX were found at 1734 and 1712 cm −1 , 1646 cm −1 , 1245 cm −1 , and 1074 cm −1 , which were corresponding to the CO stretching, CC stretching, C−N stretching, and CO stretching, respectively. 36 Comparing the spectra of zein and zein-S-S-C 2 H 4 OH, it was observed that the peaks at 1017 cm −1 , 1045 cm −1 , and 1066 cm −1 , which were all corresponding to the symmetric stretching of the S−O bond, 37−39 were shown in the spectra of zein-S-S-C 2 H 4 OH but not shown in that of zein. It was also observed that the peak at 3408 cm −1 in zein spectra, which was attributed to the −OH group, had a peak at 3300 cm −1 with higher intensity showed on its shoulder in the spectra of zein-S-S-C 2 H 4 OH.…”
Section: Table 1 Dls Results Of Zein-s-s-ptx_np and Zein_ptx_npmentioning
confidence: 98%
“…Some biocompatible polymers such as poly(lactide)-tocopheryl polyethylene glycol, chitosan and PEG, have been widely used for the tumor-targeted delivery and site-specifically release of of anticancer drugs (paclitaxel, curcumin and doxorubicin) [26][27][28]. In recent years, the use of liposomes to increase the therapeutic index of chemotheraputic drugs and to offers drug targeting and controlled release has emerged as a promising strategy against cancer [8,29,30].…”
Section: Resultsmentioning
confidence: 99%
“…Với các tính chất này, melanin đã được nghiên cứu ứng dụng trong nhiều lĩnh vực khác nhau. Trong y học, melanin có thể dùng để chống oxi hoá, kháng khuẩn, virus và chống ung thư [5][6][7][8]. Trong lĩnh vực môi trường, melanin được nghiên cứu để loại bỏ ion kim loại nặng trong nước bị ô nhiễm [9][10].…”
Section: đIện Thoại: 0866155264unclassified